On Rousseau an introduction to his radical thinking on education and politics - Wain, Kenneth (Key critical thinkers in education, 2011)
Few would want to dispute that Jean-Jacques Rousseau was one of the most fascinating figures of the Enlightenment; a man whose interests ranged over a variety of subjects, from politics, to education, to music, to botany. He was also one of the most contradictory and controversial thinkers and exciting writers of his time; the writer of the first modern autobiography and author of the best-selling novel of his day. Emile was among his most celebrated works, a book he regarded as his crowning achievement. Its revolutionary ideas have influenced radical thinkers and made him famous with generations of educators right into the twentieth century. Rousseau made other contributions to education, but his more political works on the subject are usually ignored by commentators. There has been no shortage of books about him in recent years, including general introductory ones. But a comprehensive introductory book dealing with all the aspects of his thoughts about education and politics has long been overdue. On Rousseau: an introduction to his radical thinking on education and politics fills this void, and should interest educators, educators of educators, philosophy students, and all with a general interest in education and politics and the history of ideas.